Analysis of factors influencing smoker behavior in designated non-smoking zone on campus - Leonardi, Felix; Trirasetya, Mutiara Ulfa; Suhartomi, Suhartomi; Sihotang, Widya Yanti; Edison, Rizki Edmi (MEDIA ILMU KESEHATAN, 2024)
Background: The GATS research findings indicate that tobacco use in Indonesia is the highest worldwide among teenagers, with a percentage of 34.8% consumed by individuals aged 15 and above. Tobacco companies leverage this legality to market cigarettes widely to students, including university students. Smoke-free areas are government efforts to prevent smoking on campuses.Objective: To identify determinant factors affecting non-smoking behavior among smokers in smoke-free campus areas.Methods: This research study is descriptive quantitative with a cross-sectional design. It used a purposive sampling technique with criteria of 74 male smoker students from the Faculty of Medicine and Dentistry at Universitas Prima Indonesia and was analyzed using a chi-square test.Results: The chi-square test analysis results indicated an effect between knowledge and attitude on non-smoking behavior in smoke-free campus areas with a P-value of 0.001.Conclusion: The research findings found that knowledge and attitude are determinant factors of non-smoking behavior among smokers in smoke-free campus areas.